Bevacizumab Does Not Inhibit the Formation of Liver Vessels and Liver Regeneration Following Major Hepatectomy: A Large Animal Model Study - Troup, Ondrej; Skalicky, Adam; Vistejnova, Lucie; Klein, Pavel; Maleckova, Anna; Florova, Blanka; Malkus, Tomas; Molacek, Jiri; Treska, Vladislav; Kriz, Miroslav; Zeman, Jan; Skalicky, Tomas (In vivo (Athens, Greece), 2022)
BACKGROUND/AIM: Patients with unresectable liver colorectal cancer metastases are treated with neoadjuvant chemotherapy often accompanied by biological therapy aimed at reducing the mass of metastases and thus increasing the chances of resectability. Bevacizumab comprises an anti-VEGF (vascular endothelial growth factor) humanized IgG monoclonal antibody that is used for biological therapy purposes. It acts to inhibit angiogenesis, thereby slowing down the growth of metastases. Due to its being administered systematically, bevacizumab also exerts an effect on the surrounding healthy liver parenchyma and potentially limits the process of neovascularization and thus regeneration of the liver. Since the remnant liver volume forms an important factor in postoperative morbidity and mortality following a major hepatectomy, we decided to study the effect of bevacizumab on vascular and biliary microarchitecture in healthy liver parenchyma and its ability to regenerate following major hepatectomy. MATERIALS AND METHODS: We performed an experiment employing a large animal model where a total of 16 piglets were divided into two groups (8 piglets in the control group and 8 piglets in the experimental group with bevacizumab). All the animals were subjected to major hepatectomy and the experimental group was given bevacizumab prior to hepatectomy. All the animals were sacrificed after 4 weeks. We performed biochemical analyses at regular time intervals during the follow-up period. Histological examination of the liver tissue was performed following sacrifice of the animals. RESULTS: No statistical difference was shown between groups in terms of the biochemical and immunohistochemical parameters. The histological examination of the regenerating liver tissue revealed the higher length density of sinusoids in the experimental group. CONCLUSION: Bevacizumab does not act to impair liver regeneration following hepatectomy.
Keywords: anti-VEGF; regenerace jater; Vascular Endothelial Growth Factor A; Disease Models, Animal; zvířata; prasata; humanizované monoklonální protilátky; patologická angiogeneze; Animals; lidé; Liver Neoplasms; modely nemocí na zvířatech; Antibodies, Monoclonal, Humanized; vaskulární endoteliální růstový faktor A; nádory jater; hepatektomie; hepatectomy; kolorektální nádory; liver regeneration; Colorectal Neoplasms; Humans; Bevacizumab; Liver Regeneration; Neovascularization, Pathologic; Swine; bevacizumab; Hepatectomy